Penerapan Media Pembelajaran Video Terhadap Hasil Belajar Di SMP Negeri 1 Anggoli - Pija Napitupulu (Yayasan Al-Ahliyah Al-Islamiyah Aek Badak, 2023)
The field of education is just beginning to grow, and numerous changes are being implemented to raise educational standards. The purpose of this study is to determine whether student learning outcomes may be enhanced using video learning materials. It is used to give students a fresh perspective on how to comprehend the subject matter. This kind of study employs assessments and observations as data gathering tools in classroom action research (PTK). Finding the class average (mean) and percentage methods is the data analysis methodology employed. 15% of students used congregational prayer materials to finish the Islamic Religion Subject, according to the research's pre-test data. Student learning outcomes increased in the first cycle compared to the learning outcomes prior to the activity.